2010
DOI: 10.1093/humupd/dmq009
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral biomarkers of endometriosis: a systematic review

Abstract: Peripheral biomarkers show promise as diagnostic aids, but further research is necessary before they can be recommended in routine clinical care. Panels of markers may allow increased sensitivity and specificity of any diagnostic test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
296
0
15

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(329 citation statements)
references
References 200 publications
4
296
0
15
Order By: Relevance
“…1 There is general agreement that endometriosis is a pelvic inflammatory process; however, research has suggested that endometriosis is also characterized by systemic inflammation. 4,5 Various kinds of inflammatory factors have been found to be elevated in peritoneal fluid and in the peripheral blood among women with endometriosis compared with controls. [5][6][7][8] Several case-control studies have found that women with endometriosis had higher serum levels of low-density lipoprotein (LDL) or oxidized LDL compared with controls.…”
mentioning
confidence: 99%
“…1 There is general agreement that endometriosis is a pelvic inflammatory process; however, research has suggested that endometriosis is also characterized by systemic inflammation. 4,5 Various kinds of inflammatory factors have been found to be elevated in peritoneal fluid and in the peripheral blood among women with endometriosis compared with controls. [5][6][7][8] Several case-control studies have found that women with endometriosis had higher serum levels of low-density lipoprotein (LDL) or oxidized LDL compared with controls.…”
mentioning
confidence: 99%
“…Immunity is one of the proposed factors in pathogenesis of endometriosis, so it is not surprising that inflammatory cytokines and other immunological markers have been suggested (May et al, 2010). Additional potential biomarkers being elevated in endometriosis are TGF-β1, COX-2, VEGF, ER-1α and aromatase (Meng et al, 2011), but their elevated levels are unfortunately not fully endometriosis-specific to be utilized in clinical practice.…”
Section: Immunological Markersmentioning
confidence: 99%
“…The expression level of PEDF was found to be significantly lower in the endometrium , endometrial lesions , peritoneal fluid (Chen et al 2011) and serum of women with endometriosis than that in the same organs of healthy women. On the other hand, whether VEGF is elevated in women suffering from endometriosis is still debatable (May et al 2010).…”
Section: The Role Of Pedf In Endometrial Physiology and Pathologymentioning
confidence: 99%